2018
DOI: 10.1371/journal.pone.0199034
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocytes can be activated to act as antigen presenting cells to promote anti-tumor responses

Abstract: Immune evasion by tumors includes several different mechanisms, including the inefficiency of antigen presenting cells (APCs) to trigger anti-tumor T cell responses. B lymphocytes may display a pro-tumoral role but can also be modulated to function as antigen presenting cells to T lymphocytes, capable of triggering anti-cancer immune responses. While dendritic cells, DCs, are the best APC population to activate naive T cells, DCs or their precursors, monocytes, are frequently modulated by tumors, displaying a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 46 publications
3
63
0
2
Order By: Relevance
“…The positive influence of IgG1 TIBs in KRAS mut tumors could be explained by presentation of BCR-cognate tumor antigens to CD4 + T-cells. Considered alongside recent reports revealing the importance of antigen-specific B-cells as cognate antigen presenters [6, 7, 18, 62, 63], these results support the concept that therapeutic vaccination using whole proteins or their encoding genes (including KRAS mut ) [64] could more efficiently exploit the antigen-presentation machinery of cognate B-cells. The hypothesis that mutant KRAS peptide itself is among the involved antigenic targets is especially attractive since, in contrast to other neoantigens, the driver mutation is a sensitive component of tumor survival.…”
Section: Discussionsupporting
confidence: 70%
“…The positive influence of IgG1 TIBs in KRAS mut tumors could be explained by presentation of BCR-cognate tumor antigens to CD4 + T-cells. Considered alongside recent reports revealing the importance of antigen-specific B-cells as cognate antigen presenters [6, 7, 18, 62, 63], these results support the concept that therapeutic vaccination using whole proteins or their encoding genes (including KRAS mut ) [64] could more efficiently exploit the antigen-presentation machinery of cognate B-cells. The hypothesis that mutant KRAS peptide itself is among the involved antigenic targets is especially attractive since, in contrast to other neoantigens, the driver mutation is a sensitive component of tumor survival.…”
Section: Discussionsupporting
confidence: 70%
“…In addition, it has been shown that these CD40-activated B cells are not sensitive to the immunosuppressive microenvironment [92], and that they can efficiently reach secondary lymphoid organs when injected in vivo, where they can efficiently activate T cells [93]. The potential of these CD40-activated B cells have been tested and validated in vivo in models of Human papillomavirus 16 (HPV16) E6 and E7 expressing TC-1 tumor [94], B16-F10 melanoma, E.G7 lymphoma [95], 4T1 breast tumor metastasis [96], sarcoma [25] and in spontaneous non-Hodgkin’s lymphoma in dogs [97]. In conclusion, CD40-activated B cells represent an interesting tool in cancer immunotherapy, and further studies, including clinical trials, should be performed to confirm this potential.…”
Section: Role Of B Cells In Cancer Therapymentioning
confidence: 99%
“…114,115) The use of pDNA encapsulating LNPs as an antitumor adjuvant was previously demonstrated. 116) Recently, there has been considerable interest in targeting B lymphocytes (or B cells) in the spleen. B cells not only produce antibodies and cytokines for fighting infections and inflammation, they can act as APCs for stimulating specific T cell production.…”
Section: Applications For Spleen Gene Deliverymentioning
confidence: 99%